1995
DOI: 10.1177/0013916595273001
|View full text |Cite
|
Sign up to set email alerts
|

Schoolyards

Abstract: Two groups of schoolyards for junior- and intermediate-level schools were studied. A previous study had shown that teachers considered these groups of schoolyards to be "good" and bad, respectively. It was found that the good schoolyards had woods either in or near them, whereas the bad schoolyards did not. It also was seen that children in the good schoolyards took-part In a greater number of activities than children in the bad ones. The schoolyards' different places were used with different frequency and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…A recent study of Haug et al (2008) found that children in secondary schools with many facilities had 4.49 times higher odds of being physically active compared to children in schools with fewer facilities. Lindholm (1995) and Fjørtoft and Sageie (2000) have described how green structures may motivate children's play and physical activity. This may explain the higher activity of girls in schoolyard B as they used the forest area more than the boys (Table 3).…”
Section: The Affordance Of Schoolyardsmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent study of Haug et al (2008) found that children in secondary schools with many facilities had 4.49 times higher odds of being physically active compared to children in schools with fewer facilities. Lindholm (1995) and Fjørtoft and Sageie (2000) have described how green structures may motivate children's play and physical activity. This may explain the higher activity of girls in schoolyard B as they used the forest area more than the boys (Table 3).…”
Section: The Affordance Of Schoolyardsmentioning
confidence: 99%
“…It is generally accepted that green structures have a considerable potential for promoting physical activity and improving health in adult people (Tzoulas et al, 2007). Previous studies have documented that stimulating green environments also influence children's play and physical activity (Lindholm, 1995;Fjørtoft, 2004).…”
Section: The Affordance Of Schoolyardsmentioning
confidence: 99%
See 3 more Smart Citations